FORMATION OF COGNITIVE ACTIVITY IN EARLY CHILDHOOD DEVELOPMENT OF MEANS OF INFORMATION AND COMMUNICATIONS TECHNOLOGIES - Maksimovich, М.Б. (Journal of Information Technologies in Education (ITE), 2010)
We analyzed question of formation of cognitive activity in early childhood development of means of information and communications technologies. We propose to study material by using the web-media environment «Preschooler»